STUDI TENTANG PRINSIP – PRINSIP PENEMPATAN PEGAWAI PADA DINAS PERUMAHAN DAN PEMUKIMAN KABUPATEN KUTAI TIMUR - Jamiah dan Fachriansyah (Prodi Ilmu Administrasi Negara, 2021)
In this study, using data collection techniques with library research, field studies, namely by collecting data through observation, documentation, and interviews to obtain clearer information in accordance with what is needed in the study. describe the principles of assigning employees to the Settlement and Housing Office of East Kutai Regency and to find out the inhibiting factors faced in the principles of assigning employees to the Settlement and Housing Office of East Kutai RegencyOne of the main principles of placing an employee in a position is placing the right person in the right place (The Right Man In The Right Place). However, in reality the placement of a person's position is often incorrect in their placement, as in the East Kutai Regency Settlement and Housing Office, some of the highest positions held by some of its employees do not comply with the appropriate educational standards. Taking into account the limitations of the writer's ability and time, this study focuses on the principles of assigning employees on this basis. It is hoped that employees will be more motivated to do their jobs in order to obtain new positions and assignments through an organized and healthy career development system so that a government apparatus and organization is formed. accountable and qualified.In conclusion, the principles of employee placement have been implemented quite well, but there are still obstacles in their implementation. This is evidenced by the presence of several employees who are not placed in accordance with predetermined criteria.